PEMIKIRAN MUHAMMAD ATHIYA AL-ABRASYI TENTANG PENDIDIKAN DAN RELEVANSINYA DENGAN DUNIA MODERN - Sedya Santosa; Karim Abdillah (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2021)
This study aims to determine the thoughts of Muhammad Athiya Al-Abrasyi about education and its relevance to education to education in the modern world. This research uses literature study and analytical studies to build a theoretical framework for this material. In conclusion, Muhammad Athiya Al-Abrasyi saw the importance of education and the environment for humans to facilitate the process of building morals. In this way, humans can intellectually choose and distinguish what should be done and what should be left behind. Ibn Maskawaih's thinking in education rests on the concept of education and its relation to technology.